72 Lupus impact tracker is responsive to changes in physician (T2T) and patient (SLAQ, EQ5D) relevant outcomes in a large spanish lupus registry cohort. (April 2019) - Figueroa, Iñigo Rua; Devilliers, Herve; Maria Pego Reigosa, Jose; González, Irene Altabás; Narváez-García, Javier; López-Longo, Francisco Javier; Ovalles-Bonilla, Juan; Alen, Jaime Calvo; Izquierdo, Maria Galindo; Nebro, Antonio Fernandez; Ibáñez-Barcelo, Mónica; Morales, Carlos Montilla; et al.
Abstract : Background: Remission and Low Disease activity state (LDAS) are physician assessed treat to target-T2T outcomes for Systemic Lupus Erythematosus (SLE). Lupus Impact Tracker (LIT), a ten-item unidimensional patient reported tool has good psychometric properties and responds to patient reported changes in health, physician based disease activity (DA) and composite response Index (SRI). Herein we report responsiveness of LIT to changes in physician (T2T) and patient assessed outcomes (DA by SLAQ and health status (EQ5D)) among SLE patients from the largest European SLE registry- cohort. Methods: One-year longitudinal, observational, multi-center data from 1364 adult patients with SLE meeting 1997 ACR criteria were obtained from baseline and year 1 visit. This included demographics, patient reported tools (LIT, EQ5D VAS, SLAQ), SLE (activity-SLEDAI) and medications. Remission off therapy (ROFT) was defined as SLEDAI=0 without prednisone or Immunosuppressive/s. Remission on-therapy (RONT) was SLEDAI=0 and a prednisone dose 5 mg/day and/or Immunosuppressive/s (maintenance dose). LDAS (modified) was defined as SLEDAI 4, prednisone dose 9 mg/day and/or maintenance immunosuppressive/s. Non-optimal (NO) disease status was SLEDAI >4 and/or prednisone dose >9 mg/day and/or immunosuppressive/s in induction dose. Use of hydroxychloroquine was permitted in all groups. LIT values were compared using mixed models. Responsiveness was evaluated by standard response means (SRM) in groups with changes in DA (T2T, SLAQ) and EQ5D VAS as anchors. We did not have enough observations for stratified analysis for SLE patients with fibromyalgia. Results: 1232/1364 (90%) were women, and 95% were Caucasian. Mean (SD) SLEDAI and SDI were 2.6 (3.5) and 0.7 (1.1) respectively. As (i) DA was low (median 2) in LDAS, (ii) steroid use was more prevalent in RONT than LDAS, we combined RONT and LDAS into one category to analyse patient relevant differences in LIT. LIT was responsiveness in the appropriate direction with improvement and worsening in disease activity (T2T and SLAQ) and health status (EQ5D VAS) over time. Mean LIT changes to and from NO to RONT/LDAS ranged from 3–5 (table 1 ), while it declined by over 8.5 with change from NO to ROFT. We had limited observations for ROFT to NO change. Mean change in LIT ranged from −3 to 3 with improvement and worsening in SLAQ, and from −7.6 to 6 with improvement and worsening in EQ5D VAS. Conclusions: LIT responds appropriately in both directions to changes in physician (T2T) as well as patient relevant (DA and health status) outcomes among Spanish SLE patients. Funding Source(s): None